Why study A Level Religious Studies? Qualitative perspectives from two English Midlands sixth forms. Issue 1 (2nd January 2017) - Jones, Ian
Abstract: Religious Studies (RS) is expected to impact students' personal development as well as enabling acquisition of knowledge and understanding of religious and philosophical traditions. But to what extent does this actually occur? As part of a larger quantitative investigation of the effects of A Level RS in students' beliefs, values and worldviews through a large-scale questionnaire survey of AS students, a small-scale, in-depth piece of qualitative research was undertaken with A Level RS students in two Midlands sixth forms. Through semi-structured interviews and classroom observation, it explores students' motivations for studying A Level RS, the value they see in the subject and how far they perceived themselves changed as a result. Students appreciated the scope to discuss and debate, and the potential wider applicability of the subject. All students felt they had their own stance both challenged and confirmed, although there also appeared to be limiting factors as to how far understanding of, and empathy for, the beliefs, values and worldviews of others was possible.